Classification of Performance Grades of High Modulus Asphalt and Its Mixture: Taking China as an Example - Lu Zhou; Kaixi Duan; Feng Gao; Yi Fu; Qian Chen (Advances in Materials Science and Engineering)
With the increase in traffic volume and axle load, the requirement of road quality is continuously improving, and high modulus asphalt has attracted the attention of researchers due to its excellent road service performance and economic benefits. In order to further improve the durability and use quality of Chinese roads, realize the scientific evaluation of the performance of high modulus asphalt and its mixture, and further promote the development of high modulus asphalt technology in China, the performance indexes of high modulus asphalt and its mixture in China were comprehensively investigated. The differences in high- and low-temperature performance of matrix asphalt, basic modified high modulus asphalt, and composite modified high modulus asphalt were compared and evaluated. Based on the results of mathematical statistics and the relevant specifications of high modulus asphalt in China, the performance grades of high modulus asphalt and its mixture were proposed. The results showed that compared with the basic asphalt, the softening points of the basic modified high modulus asphalt and the composite modified high modulus asphalt were increased by 18.76% and 82.89%, respectively, and the rutting factors were increased by 2 and 9 times, respectively, but the improvement effect of the low-temperature performance of the high modulus asphalt was not obvious. Based on the data statistics node and relevant Chinese regulations, high modulus asphalt and its mixtures were divided into four grades: excellent, good, fair, and poor, aiming to provide scientific suggestions for the wide application of high modulus asphalt.